Bilateral pulmonary emboli in an amateur kick boxer: A case report and literature review - Elabbass A. Abdelmahmuod (14777296) (2023)
Increased knowledge of unusual pulmonary embolism presentations in athletes will prevent delays in the diagnosis and management. Other Information Published in: Clinical Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1002/ccr3.4733